2000
DOI: 10.1104/pp.124.1.461
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sulfur Nutrition in Wild-Type and Transgenic Poplar Over-Expressing γ-Glutamylcysteine Synthetase in the Cytosol as Affected by Atmospheric H2S

Abstract: This study with poplar (Populus tremula ϫ Populus alba) cuttings was aimed to test the hypothesis that sulfate uptake is regulated by demand-driven control and that this regulation is mediated by phloem-transported glutathione as a shoot-toroot signal. Therefore, sulfur nutrition was investigated at (a) enhanced sulfate demand in transgenic poplar over-expressing ␥-glutamylcysteine (␥-EC) synthetase in the cytosol and (b) reduced sulfate demand during short-term exposure to H 2 S. H 2 S taken up by the leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 48 publications
3
82
0
2
Order By: Relevance
“…Glutathione and sulfate are both translocated within the sieve sap (Rennenberg et al, 1979), although glutathione is the major form of long-distance transport of reduced S in plants (Rennenberg et al, 1979;Herschbach et al, 2000). Interestingly, split-root experiments revealed that glutathione content in the 2S side of the split-roots, unlike sulfate content, remains high, and is comparable to the glutathione content of 1S/1S control roots (Fig.…”
Section: Role Of Glutathione In the Regulation Of Sultr11 And Sultr12mentioning
confidence: 89%
See 2 more Smart Citations
“…Glutathione and sulfate are both translocated within the sieve sap (Rennenberg et al, 1979), although glutathione is the major form of long-distance transport of reduced S in plants (Rennenberg et al, 1979;Herschbach et al, 2000). Interestingly, split-root experiments revealed that glutathione content in the 2S side of the split-roots, unlike sulfate content, remains high, and is comparable to the glutathione content of 1S/1S control roots (Fig.…”
Section: Role Of Glutathione In the Regulation Of Sultr11 And Sultr12mentioning
confidence: 89%
“…However, such a negative effect of glutathione on the root sulfate uptake capacity was not observed in poplar after an exposure of aerial organs to H 2 S, although this treatment was shown to significantly increase leaf and root glutathione contents (Herschbach et al, 2000;Westerman et al, 2001). Also, the overexpression of the key enzyme for glutathione synthesis, g-glutamyl-Cys synthase, which resulted in the overaccumulation of glutathione, did not induce any down-regulation of the expression of sulfate transporters (Herschbach et al, 2000;Hartmann et al, 2004). Finally, increasing the glutathione content by providing O-acetyl-Ser to barley (Hordeum vulgare) plants did not result in a reduction in either the transcript accumulation of sulfate transporters or the sulfate uptake .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The demand of developing seeds for sulfur can potentially be satisfied either through supply of sulfate or, alternatively, in the form of reduced phloemmobile sulfur compounds. Potential transport metabolites for reduced sulfur are GSH (Rennenberg, 1982;Herschbach et al, 2000) and S-methylmethionine (Bourgis et al, 1999). It has been proposed that glutathione translocated from shoot to root via the phloem acts as a signal responsible for repression of sulfate uptake in the roots (Lappartient and Touraine, 1997;Lappartient et al, 1999).…”
mentioning
confidence: 99%
“…Furthermore, glutathione translocated in the phloem is suggested to mediate transmission of the interorgan signal of sulfur status in vascular plants (Lappartient et al, 1999). Studies with poplar more recently suggested a correlation between the demand of sulfur in shoots and the sulfate to glutathione ratio in the phloem sap (Herschbach et al, 2000).…”
mentioning
confidence: 99%